OPTIMALISASI WEBSITE DESA DALAM EFISIENSI PELAYANAN, POTENSI DESA DAN PENINGKATAN SUPPLAY BARANG DI DESA KARANGJATI PASURUAN - Arif Faizin; Muh. Aniar Hari Swasono (Jurnal Abdimas Sangkabira, 2022)
To carry out community service activities in Karangjati Pandaan Village to help optimize village potential, village services, and community production by making village website applications. The village website is a village information system in the digital era that contains news, photos, and videos that the wider community can access anytime and anywhere. With the village website, it is hoped that all forms of services in the village are easier to implement. The potential and results of community products in the village are more easily recognized by outsiders as village promotion materials and increase the supply of goods outside the area. The method used in community service activities in Karangjati Pandaan Village is the method of observation, interviews, and literacy studies which are expected to explore all the data and potential in the village, which we will develop through the village website that has been created. The result of this community service activity in Karangjati Pandaan Village is the formation of a village website which is expected to facilitate village services, develop potential and increase the supply of goods to lift the community's economy.